2009
DOI: 10.1253/circj.cj-09-0324
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Receptor Blocker, Valsartan, Increases Myocardial Blood Volume and Regresses Hypertrophy in Hypertensive Patients

Abstract: eft ventricular hypertrophy (LVH) strongly predicts cardiovascular morbidity and mortality in patients with hypertension (HT). Rates of cardiovascular events have been reported as 2-to 4-fold higher in the presence of LVH in patients with HT, independent of standard risk factors. 1,2 Moreover, regression of hypertensive LVH is associated with improved prognosis, 3,4 so prevention or reversal of LVH in patients with HT is widely accepted as a desirable treatment goal.LVH associated with HT arises from hypertrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…27 Another recent report has also shown that mean blood volume measured on myocardial contrast echocardiography, an indicator of the myocardial microvascular narrowing, is decreased in hypertensive patients with LVH, and valsartan corrects the decreased mean blood volume in those patients. 28 These facts might therefore account for the enhanced reduction of cardiovascular events, particularly angina pectoris, by valsartan in hypertensive patients with LVH.…”
Section: Shiraishi J Et Almentioning
confidence: 99%
“…27 Another recent report has also shown that mean blood volume measured on myocardial contrast echocardiography, an indicator of the myocardial microvascular narrowing, is decreased in hypertensive patients with LVH, and valsartan corrects the decreased mean blood volume in those patients. 28 These facts might therefore account for the enhanced reduction of cardiovascular events, particularly angina pectoris, by valsartan in hypertensive patients with LVH.…”
Section: Shiraishi J Et Almentioning
confidence: 99%
“…We previously revealed that the renin-angiotensin system, as evaluated by the tissue levels of angiotensin-converting enzyme and AT1 receptor and the plasma levels of renin and angiotensin II, was activated in the n/i/eNOS -/-mice. 10, 33 The renin-angiotensin system plays an important role in the pathogenesis of heart diseases. 34, 35 Based on the evidence, we further tested our hypothesis that the AT1 receptor signal transduction pathway mediates cardiac abnormalities in the n/i/eNOS -/-mice.…”
Section: Role Of At1 Receptor Pathway In the Development Of Cardiac Pmentioning
confidence: 99%
“…22 In the heart, LVH might be analogous to renal damage because longstanding exposure to high BP leads to LVH. 23 We previously reported that LVH was strongly associated with the risk of cerebrovascular events (adjusted HR: 2.38; 95%CI: 1.62-3.48; P<0.001). 10 Furthermore, higher urinary albumin excretion has been observed in patients with LVH, 24,25 suggesting that cardiac and glomerular vascular damage might occur concurrently.…”
Section: Discussionmentioning
confidence: 86%